2015
DOI: 10.1109/tnsre.2015.2398112
|View full text |Cite
|
Sign up to set email alerts
|

Is it Finger or Wrist Dexterity That is Missing in Current Hand Prostheses?

Abstract: Building prostheses with dexterous motor function equivalent to that of the human hand is one of the ambitious goals of bioengineers. State of art prostheses lack several degrees of freedom (DoF) and force the individuals to compensate for them by changing the motions of their arms and body. However, such compensatory movements often result in residual limb pain and overuse syndromes. Significant efforts were spent in designing artificial hands with multiple allowed grasps but little work has been done with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 37 publications
3
94
0
Order By: Relevance
“…Since the forearm contains muscles that move both the fingers and the wrist, the user must generate EMG activity to control the prosthetic fingers without significant wrist movement, which may generate myoelectric signals that disrupt control [8]. One recent study showed that when non-amputees are limited to two degrees of freedom at the wrist (pronation/supination and flexion/extension) and 1° of freedom at the hand (open/close), they perform similarly to when they are limited to a 1°-of-freedom rotating wrist coupled with their natural 22°-of-freedom hand [13]. Thus, a clinically successful partial-hand pattern recognition control system must both provide high performance accuracy and allow the individual to retain use of their wrist.…”
Section: Introductionmentioning
confidence: 99%
“…Since the forearm contains muscles that move both the fingers and the wrist, the user must generate EMG activity to control the prosthetic fingers without significant wrist movement, which may generate myoelectric signals that disrupt control [8]. One recent study showed that when non-amputees are limited to two degrees of freedom at the wrist (pronation/supination and flexion/extension) and 1° of freedom at the hand (open/close), they perform similarly to when they are limited to a 1°-of-freedom rotating wrist coupled with their natural 22°-of-freedom hand [13]. Thus, a clinically successful partial-hand pattern recognition control system must both provide high performance accuracy and allow the individual to retain use of their wrist.…”
Section: Introductionmentioning
confidence: 99%
“…Partial-hand amputees often retain the ability to move their wrists, and preservation of residual wrist motion is critical for functional everyday activities. Montagnani et al ( 2015 ) showed that when non-amputees are limited to two degrees of freedom at the wrist (pronation/supination and flexion/extension) and one degree of freedom at the hand (open/close), they perform similarly to when they are limited to a one degree-of-freedom wrist (rotation) coupled with their intact, twenty-two degree-of-freedom hand. Thus, a clinically successful partial-hand pattern recognition control system must maintain high performance while allowing the individual to use their wrist.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the movements included in the original dataset are missing in some cases that could potentially improve the estimation of the dimensionality of forearm muscles, a notable one being the extension of all ngers. Also, the dataset includes only a few movements that focus on coordinated motion of the ngers and wrist, which are functionally important for manual dexterity [46]. Future studies that quantify muscle control capabilities in amputees should consider these limitations and adjust the experimental protocol accordingly.…”
Section: Methodological Limitationsmentioning
confidence: 99%